Cell types involved in allergic asthma and their use in in vitro models to assess respiratory sensitization - Verstraelen, S.; Bloemen, K.; Nelissen, I.; Witters, H.; Schoeters, G.; Heuvel, R. Van Den (Toxicology in vitro, 2008)
This review first describes the mechanism and cell types involved in allergic asthma, which is a complex clinical disease characterized by airway obstruction, airway inflammation and airway hyperresponsiveness to a variety of stimuli. The development of allergic asthma exists of three phases, namely the induction phase, the early-phase asthmatic reaction (EAR) and the late-phase asthmatic reaction (LAR). In the induction phase, antigen-presenting cells play a major role. Most important cells in the EAR are mast cells, and during the LAR, various cell types, such as eosinophils, neutrophils, T cells, macrophages, dendritic cells (DCs), and cells that endow structure are involved. In occupational asthma, this immunological mechanism is involved in 90% of the cases. The second part of this review gives an overview of in vitro models to assess the hazardous potential of high- and low-molecular weight chemicals on the respiratory system. In order to develop a good in vitro model for respiratory allergy, the choice of appropriate cell types is important. Epithelial cells, macrophages and DCs are currently the most used models in this field of research.